HUBUNGAN HUKUM DAN EKONOMI DALAM ISLAM: TINJAUAN ATAS KAIDAH HUKUM BIDANG PEREKONOMIAN - Mujaddidi, Ah. Shibghatullah (IAIN Tulungagung, 2020)
This study aims to describe the relationship of law and economics in Islam. The research method used is a literature review approach sourced from credible journals and other relevant reading sources. The results of this study indicate that sharia economics not only acts as a science but also as a system so as to achieve its objectives it requires maximum effort and strategies to restructure the socio-economic system comprehensively. The restructuring must be accompanied by efforts to reform the political, legal, economic and social systems by involving the participation of all citizens. In some cases these include the application of the principle of buying and selling in working capital, the application of the mudharabah principle in investment or the application of bai 'as-salam in the construction of a project. Along with the development of the law era, it is demanded to be able to manipulate society or vice versa, the law is able to control the community to be aware of the law and the creation ofjustice.